A Survey on the Relationship between Ocean Subsurface Temperature and Tropical Cyclone over the Western North Pacific - Difu Sun; Junqiang Song; Kaijun Ren; Xiaoyong Li; Guangjie Wang (Advances in Meteorology)
The relationship between ocean subsurface temperature and tropical cyclone (TC) over the western North Pacific (WNP) is studied based on the TC best-track data and global reanalysis data during the period of 1948–2012. Here the TC frequency (TCF), lifespan, and genesis position of TCs are analysed. A distinctive negative correlation between subsurface water temperature and TCF is observed, especially the TCF in the southeastern quadrant of the WNP (0–15°N, 150–180°E). According to the detrended subsurface temperature anomalies of the 125 m depth layer in the main TC genesis area (0–30°N, 100–180°E), we selected the subsurface cold and warm years. During the subsurface cold years, TCs tend to have a longer mean lifespan and a more southeastern genesis position than the subsurface warm years in general. To further investigate the causes of this characteristic, the TC genesis potential indexes (GPI) are used to analyse the contributions of environmental factors to TC activities. The results indicate that the negative correlation between subsurface water temperature and TCF is mainly caused by the variation of TCF in the southeastern quadrant of the WNP, where the oceanic and atmospheric environments are related to ocean subsurface conditions. Specifically, compared with the subsurface warm years, there are larger relative vorticity, higher relative humidity, smaller vertical wind shear, weaker net longwave radiation, and higher ocean mixed layer temperature in the southeastern quadrant during cold years, which are all favorable for genesis and development of TC.